2014
DOI: 10.1007/s00264-014-2481-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intervertebral disc regeneration with implantation of bone marrow mesenchymal stem cells (BMSCs) using quantitative T2 mapping: a study in rabbits

Abstract: Transplantation of BMSCs was able to promote the regeneration of degenerative discs. Quantitative and non-invasive T2 mapping could be used to evaluate the regeneration of the nucleus pulposus with good sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…With increasing knowledge on stem cell transplantation, cell-based therapeutic approaches are becoming promising strategies for IVDD regeneration [5,6]. Another stem cellbased approach, which has been applied to the regeneration of many other tissues, aims to promote endogenous stem cell migration to the target area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing knowledge on stem cell transplantation, cell-based therapeutic approaches are becoming promising strategies for IVDD regeneration [5,6]. Another stem cellbased approach, which has been applied to the regeneration of many other tissues, aims to promote endogenous stem cell migration to the target area.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are highly studied stem cells of different origins, including synovium, periosteum, skeletal muscle, and adipose tissues. Our previous studies demonstrated the excellent repair efficiency of BMSCs transplanted into rabbit intervertebral discs (IVDs) [6]. Besides, adiposederived stem cells have also been extensively used for repair of IVDD with the advantage of convenient availability and abundance [7], and even improve the viability of nucleus pulposus cells in degenerated intervertebral discs [8].…”
Section: Introductionmentioning
confidence: 99%
“…IVD degeneration is currently known as an age-related process which is accelerated by excessive mechanical loading [Guehring et al, 2010;Purmessur et al, 2013], disc injury [Yang et al, 2009;Cai et al, 2015], oxidative stress [Nasto et al, 2013], diabetes [Jiang et al, 2013], chronic tobacco smoking , obesity [Samartzis et al, 2012], and genetic inheritance [Kalichman and Hunter, 2008]. Given that the IVD mainly functions to transmit and absorb mechanical loading onto the spine, our hypothesis provides an illustrative model that depicts the biological function and disappearance of cytoplasmic vacuoles, highlighting a mechanical exhaustion of notochordal cell resources (Fig.…”
Section: Significance and Limitations Of The Hypothesismentioning
confidence: 99%
“…2, 3A). The results obtained by others for these two macromolecules differ between reports and largely depend on the BM-MSC growth conditions [30,48]. SOX9, responsible for the induction of type II collagen expression later during chondrogenic differentiation, is the most widely used marker in the evaluation of MSC differentiation to chondrocyte-like cells [49].…”
Section: Discussionmentioning
confidence: 93%
“…We have also investigated CD271 -MSCs and compared these cells to the entire population of MSCs generated by plastic adherence [29][30][31] …”
Section: Cd271 Mscs In Ivd Regenerationmentioning
confidence: 99%